KEGIATAN PEDULI LINGKUNGAN DENGAN PEMBERSIHAN SAMPAH PADA KAWASAN PESISIR PULAU ISAU (PULAU TUJUH) PASANEA KABUPATEN MALUKU TENGAH - Soselisa, Fanny; Tetelay, Febian; Sahupala, Andjela; Siahaya, Troice; Irwanto, Irwanto; Pattinasarany, Cornelis K; Louhenapessy, Fredy Hendry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
The problem of waste at tourist attractions has from the past until now is still a hot topic in the world of tourism. Starting from pollution of marine ecosystems, air pollution, to direct impacts on human health. To create tourism that can guarantee the preservation of nature and culture, a sustainable tourism concept is needed. The aim of this activity is to clean the coastal area of ​​Isau Island (Seven Islands) from existing rubbish, provide an example for tourists (visitors), especially local and domestic tourists, to keep the area clean and beautiful and prevent plastic waste from entering the sea and can disrupt marine ecosystems. The implementation method used is the participant method. Where participants are subjects involved in activities as participants in providing responses to activities carried out and supporting the achievement of goals and are responsible for their involvement. And the types of waste found on the coast of Isau Island Beach (Nusa Itu Resort) Pulau Tujuh Pasanea, Central Maluku Regency, there are seven types of waste materials including plastic, metal or aluminum, cloth, glass and ceramics, metal, paper and cardboard, rubber, other materials. . Plastic is a type of waste material with the highest density value. The high density of plastic waste with less efficient waste management patterns makes Isau Island Beach easy or vulnerable to environmental pollution.